Relationship between intrinsic motivation and attitude towards self- efficacy in essay writing of English language among primary school pupils - Terpari, Ravathi (2021)
This study discusses on the intrinsic motivation and attitude towards self-efficacy in essay writing of English language among primary school pupils. English is one of the most important language and one of the most important subjects some countries. However, this English has become one of the difficult subjects for pupils especially in writing. Motivation and intrinsic attitude of pupils are two important factors that increase the potential of students in essay writing. Consequently, the purpose of this study is to determine the level of intrinsic motivation and attitude level towards self-efficacy in essay writing in English language. A quantitative approach was used to conduct this study whereby a total of 169 respondents of Year 5 pupils from primary schools were chosen to be the respondents of the study. Three types of instruments which is Intrinsic Motivation Inventory (IMI), Writing Attitude Survey (WAS) and General Self-Efficacy (GSE) were adapted and utilised in this context of the study. The data obtained were analysed using descriptive and inferential analysis. The results of the findings indicated that the primary school pupils in Kluang districts have moderate level of intrinsic motivation and attitude towards self-efficacy in essay writing. In addition, there is a significant predictor of intrinsic motivation and attitude toward self-efficacy in English essay writing. The findings of this study have implication towards teaching and learning of teachers and primary school pupils.